Use of Trichoderma spp. for biological control of the livestock feed contaminant fungus Fusarium proliferatum - Ruocco M; Pane F; Ritieni A; Lanzuise S; Ambrosino P; Marra R; Woo S L; Ciliento R; Soriente I; Ferraioli S; Scala F; Lorito M (浙江大学学报. 农业与生命科学版)
Fusarium spp. are pathogens of many important agricultural crops, and are often strong my cotoxin producers. Fusarium proliferatum, in particular, causes disease in cereals and secretes the toxin Beauvaricin that contaminates livestock feed and cereals, producing a variety of toxicity symptoms ranging from poor weight gain to mortality. Beauvaricin is a cyclodepsipeptide and acts as a potent mycotoxin known to have insecticidal properties. This compound is highly toxic to human cell lines, where it induces apoptosis and specifically inhibits cholesterol acetyltransferase. Nothing is known about the role of this mycotoxin during the interaction of F. proliferatum with other microorganisms, including the fungal antagonists Trichoderma spp. In vitro tests have demonstrated that the antagonistic and mycoparasitic activity of Trichoderma is not inhibited by the presence of Beauvaricin at concentrations up to 10 mg/kg in the substrate. In vivo biocontrol assays on barley and wheat with Trichoderma against F. proliferatum isolates, producing and non-producing Beauvaricin, confirmed the ability of the antagonist to control this pathogen in all cases. Also Trichoderma culture filtrates obtained in conditions that promote Cell Wall Degrading Enzyme (CWDE) secretion, were able to inhibit spore germination of different F. proliferatum isolates. These results suggest the possibility of using Trichoderma and/or its metabolites to control contaminants of livestock feed by mycotoxin-producing Fusarium.